1997
DOI: 10.1071/zo96063
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Components of the Milk of the Tammar Wallaby (Macropus eugenii)

Abstract: The cellular components of colostrum and milk of the tammar wallaby (Macropus eugenii) have been investigated over the period of oestrus, lactation and weaning. Macrophages, neutrophils, lymphocytes and other vacuolated mononuclear cells were identified. The total number and diversity of cells were higher in colostral secretions and in secretions from post-lactational mammary glands. Neutrophils were the predominant cell type in early secretions. Macrophages were more prevalent in the milk of animals that no l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Clearly, stripe-faced dunnarts must therefore be dependent on non-specific defence mechanisms that they have, and as yet are unidentified, as well as maternal strategies. Some of these strategies may involve immunoglobulins [Deane and Cooper, 1984] and immunological cells of maternal origin in the milk [Young et al, 1997;Young and Deane, 2001], as well as possible pouch secretions [Bobek and Deane, 2002], as they have been described in other marsupial species. These maternal strategies do however require further investigation in this species.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, stripe-faced dunnarts must therefore be dependent on non-specific defence mechanisms that they have, and as yet are unidentified, as well as maternal strategies. Some of these strategies may involve immunoglobulins [Deane and Cooper, 1984] and immunological cells of maternal origin in the milk [Young et al, 1997;Young and Deane, 2001], as well as possible pouch secretions [Bobek and Deane, 2002], as they have been described in other marsupial species. These maternal strategies do however require further investigation in this species.…”
Section: Discussionmentioning
confidence: 99%
“…A functional immune system is not necessary for prenatal marsupials, however, at birth the young possum must exit the vagina and crawl up the maternal fur to a pouch rich in potentially pathogenic micro-organisms (Old and Deane 1998). It is obvious that maternal strategies including immunoglobulins present in the milk (Deane and Cooper 1984;Deane et al 1990;Adamski and Demmer 1999) and possibly some cells found in metatherian milk (Young et al 1997;Young and Deane 2001) play a large role in immunological protection of early pouch young. Innate immunity and passive acquired immunity must also therefore be crucial in the early survival of the young marsupials.…”
Section: Discussionmentioning
confidence: 97%
“…Neutrophils were the predominant cell type in early milk and colostrum samples, while macrophages were observed in high numbers in postlactational mammary gland secretion samples. Lymphocytes were not observed in the colostral phase, but were observed in early and late milk samples, and eosinophils were observed in all samples collected (Young et al, ).…”
Section: Mucosal鈥恆ssociated Lymphoid Tissuesmentioning
confidence: 98%
“…Immunological cells and molecules, including immunoglobulins and neutrophils that are provided to the pouch young via maternal milk during pouch life are also suggested to be important for protection of the young animal (Old and Deane, ) and normal GIT development. In the tammar wallaby, Young et al, () found that the number and diversity of cells identified in the milk varied over time, and these changes reflected different developmental stages of the young in the pouch. Neutrophils were the predominant cell type in early milk and colostrum samples, while macrophages were observed in high numbers in postlactational mammary gland secretion samples.…”
Section: Mucosal鈥恆ssociated Lymphoid Tissuesmentioning
confidence: 99%